The pleurophocercous cercariae infection in snail Family Thiaridae Grey, 1847 Northern, Thailand - Chontananarth T. (2017)
© 2017 by the Asian Pacific Journal of Tropical Disease. Objective: To investigate the prevalence of pleurophocercous cercariae infection in thiarid snails from natural infection in 12 provinces of Northern Thailand. Methods: The snail specimens were collected and examined for pleurophocercous cercariae infection using crushing method. The morphological characteristics of cercariae, which were identified by a light microscope and illustration were done using a camera lucida. Results: Based on a sample of 2 075 thiarid snails of four snail species, it was found that Melanoides tuberculata, Tarebia granifera, Thiara scabra, and Adamieta hoesei served as the first intermediate hosts of heterophyid trematode with an overall prevalence of 14.78%, revealing four different morphological characteristic types. Pleurophocercous cercaria Type I had the highest the prevalence (13.06%), followed by the pleurolophocercous cercaria Type II (0.29%), pleurolophocercous cercaria Type III (0.05%), and pleurophocercous cercaria Type IV (1.4%), respectively. Conclusions: This research report will serve a preliminary step providing new and fundamental information regarding the current geographical distribution trends of opisthorchiid and/or heterphyid trematodes infection. The findings of this study will be useful to the development of effective control measures for this type of parasitic infection in Northern Thailand.